Ideology and COVID-19 Vaccination Intention: Perceptual Mediators and Communication Moderators. Issue 6 (3rd June 2022) - Jiang, Xiaoya; Hwang, Juwon; Su, Min-Hsin; Wagner, Michael W.; Shah, Dhavan
Abstract : Widespread COVID-19 vaccination is critical to slow the spread of the illness. This study investigates how political ideology is associated with COVID-19 vaccine intention via perceived effectiveness of the vaccine, perceived side effects, and perceived severity of the illness, three key aspects of the Health Belief Model (HBM). This study also examines how partisan information flow moderates the effects of ideology on these three HBM components. Using survey data collected from two battleground states in the 2020 election (N = 1849), regression, mediation and moderation analyses revealed that conservatives were less likely to intend to get vaccinated against COVID-19, and this association was significantly mediated by perceived effectiveness and perceived side effects of vaccination, as well as perceived severity of COVID-19. In addition, partisanship of news sources and discussion partners were significant moderators of ideology's association with perceived vaccine effectiveness, with conservatives viewing COVID-19 vaccination as less effective if they were frequently exposed to liberal news, and if they had frequent conversations with fellow conservatives. This suggests boomerang effects for cross-cutting mass media exposure, and reinforcement effect for interpersonal communication. Implications for efforts to promote COVID-19 vaccine uptake are discussed, including tailored and targeted campaign strategies.